Основные методологические проблемы внедрения корпоративных информационных систем при реорганизации предприятий республики Крым - Власюк, В.В.; Попов, В.Б. (Культура народов Причерноморья, 2014)
Рассматриваются вопросы внедрения корпоративных автоматизированных систем
управления на производственных и офисных предприятиях. Особое внимание уделяется целям внедрения,
основным принципам успешного внедрения корпоративных ERP-систем на предприятиях,
оптимизационным проблемам внедрения. Розглядаються деякі з основних питань впровадження автоматизованих систем управління
на виробничих і торговельних підприємствах, а саме: цілі впровадження, основні завдання і проблеми,
принципи успішного впровадження корпоративних інформаційних ERP-систем, оптимізаційні проблеми
впровадження. Discusses some of the main issues of automated control systems for industrial and commercial
enterprises. Particular attention is paid to the introduction of targets, the basic principles of successful
implementation of corporate ERP-systems in enterprises, the introduction of optimization problems. Selection of
the corporate information system is an extremely complex conceptual task that requires serious research
organization, processes, business processes and articulating requirements for corporate information system. It
should be noted that not formalized the process of optimizing the implementation of corporate information
systems in modern enterprises and organizations. The aim of this work is to study and classification of the main
methodological problems in the implementation of ERP systems in modern enterprises and the development of
optimization methods and algorithms to solve them. According to experts one of the major problems that arise in
the implementation of enterprise systems, is the inefficiency of implementation. This is the main problem and
suggests that any modern high technology will be useful only if it is a competent implementation and use. In
many enterprises that have spent huge amounts of money to acquire and bring ERPII-systems, their launch has
only led to negative results. According to experts ERPII-systems are vital for businesses, but the success of the
implementation depends on whether it was possible to adapt them as close as possible to what is happening in
the enterprise production processes and business processes. Existing ERPII-systems, as well as in many other
applications of information, laid typical algorithms of automated business processes, which often do not
correspond to the real technological processes of the organization, for which the selection and implementation
ERPII-system. Given the existence of most organizations of its historical business processes and specific
characteristics of the business environment, the optimization of technological processes implemented in the
organization under ERPII-systems, a formal model is not always possible. As a result, when deciding on the
implementation of the ERP-system is necessary to consider not only the existing problems to be solved with the
help of business applications, but also a set of criteria that do not meet the typical business processes.
An important and urgent is the development of formal methods and mathematical models of the process of
implementing software and information systems. The process of formalizing the implementation phase of the
system can improve efficiency by several times. ERPII-effectiveness of implementing the system is achieved
through the following.
 Reduces the number of stocks as a result of finding the optimal batch purchases and balances stock on hand,
the increase in savings in storage reserves of up to 50%.

 It accelerates the turnover of capital in the 2 to 2.5 times.

 Frees the funds that go into the production development.
 Formed an objective financial statements.
 Optimize the amount of work in process and shortens the production cycle in 2 - 3 times.
 Improves customer service by optimizing the system of orders of finished products.
 Reduce the length of the closure periods for 5 - 10 days.
When choosing a ERPII-systems is necessary to understand that automation for automation does not make
sense. It should be clear that the best in the world ERPII-system can not solve all the problems of the company.
Any ERPII-system - is, first and foremost, a tool for improving the efficiency and quality of enterprise
management, making the right strategic and tactical decisions on the basis of the automated processing of
relevant and reliable information. At the same time, ERPII-system – it's not only the tools for business, but
technology and its management.